Understanding the Institution of Marriage (Indian Journal of Mass Communication and Journalism (IJMCJ), 2024)
The main objective of this research paper is to acquire an efficient understanding of the institution of marriage. This is regarded as an important institution, which individuals are required to enter into, belonging to all communities, categories and socio-economic backgrounds. The individuals normally have the major objective of making this institution successful. For this purpose, they are required to take into account various factors, i.e. communicating with others in a polite and decent manner; treating each other with respect and courtesy; making provision of factual information and depicting the traits of helpfulness and co-operation. These are regarded as essential in reinforcing cordiality and amiability in terms and relationships. The members of the family within marital homes need to ensure, they form positive viewpoints in terms of various factors. Furthermore, they need to reinforce clarity of mind. One of the important aspects that needs to be taken into account is, one should not possess any types of negative feelings in terms of each other. In addition, one needs to be well-informed in terms of peaceful conflict resolution methods. These are necessary in creating peaceful environmental conditions within homes. Therefore, through acknowledging and implementing certain factors, institution of marriage will be successful. The main concepts that are taken into account in this research paper are, understanding the meaning and significance of institution of marriage, measures to be implemented in making the institution of marriage successful and advantages of making the institution of marriage successful.